A barcode scanning mobile application for searching halal information of food products - Abd Razak, Mohd Nur Faiz; Katuk, Norliza (2017)
The rapid growth of Muslim population and global halal food market has increased the need for mobile applications that capable of checking the halal status of the food product.For this purpose, Jabatan Kemajuan Islam Malaysia (JAKIM) developed a mobile application named myJakim.The application is useful, and it provides the information that consumers need. However, it uses text-based searching which is prone to input errors. Consumers might key-in the wrong spelling of the product which causes the system to return null searching results.This paper proposes a solution to this problem by implementing a barcode scanning functionality that allows the mobile application to capture the product information automatically. A mobile application named Halal Detector was developed. An evaluation was conducted to measure the usability of Halal Detector.The results suggest that the barcode scanning facility in Halal Detector is usable and helps consumers to search the halal status of food product faster than the text-based application.